A study on FTTH implementation and migration in Nepal - Khatiwoda, Naba Raj; Dawadi, Babu R (Journal of Engineering Issues and Solutions, 2021)
The increasing demand of high speed data results into extensive enhancement on different telecommunication technologies through wireline and wireless technologies. Optical Fiber technology is being popular for fixed broadband technologies and for backhaul network data for network convergence and media device interaction. Fiber to the home (FTTH) is gaining momentum of deployments in many countries all around the world. Passive optical network (PON) utilizes point to multipoint (P2MP) topology and is becoming suitable, cost effective, and promising solutions as compared to existing copper based telecommunication infrastructure. PON architecture is cheaper than other architectures due to dynamic bandwidth allocation and common resources that can be used by different subscribers and especially for home subscribers. This paper presents a study on the effective deployment of PON based FTTH network at Nepal by referring the deployment scenario of Nepal Telecom (NT), while this network design, deployment, and implementation provides a lesson learn for cost effective deployment of such network to other stakeholders of developing countries having similar territory and implementation challenges.